Induction of Angiopoietin-2 after Spinal Cord Injury - Lee-Durham, J.C. (2011)
Angiopoietin 1 (Ang-1) and angiopoietin 2 (Ang-2) have opposing effects on blood vessels, with Ang-2 being mainly induced during the endothelial barrier breakdown. It is known that spinal cord injury (SCI) induces lasting decreases in Ang-1 levels, underlying endothelial barrier disruption, but the expression of Ang-2 in spinal cord injury has not been studied. We characterized Ang-2 after SCI using a clinically relevant rat model of contusion SCI. We found that SCI induces marked and persistent upregulation of Ang-2 (up to 10 weeks after SCI), which does not reflect well-characterized temporal profile of the blood-spinal cord barrier (BSCB) breakdown after SCI, and thus suggests other role(s) for Ang-2 in injured spinal cords. Furthermore, we also found that higher Ang-2 levels were associated with more successful locomotor recovery after SCI, both in SCI rats with markedly better spontaneous motor recovery, and in SCI rats receiving a neuroprotective pharmacological intervention (amiloride), suggesting a beneficial role for Ang-2 in injured spinal cords. Immunocytochemical analyses revealed that Ang-2 was not induced in endothelial cells, but in perivascular and non-vascular cells labeled with glial fibrillary acidic protein (GFAP) or with chondroitin sulfate proteoglycan (NG2). Therefore, it is unlikely that induction of Ang-2 contributes to vascular dysfunction underlying functional impairment after SCI, but rather that it contributes to the beneficial pro-angiogenic and/or gliogenic processes underlying recovery processes after SCI.